The Factors of Influence the Risk of Abnormal Working Hours for the Workforce in Batam City - Ridha Amalia Hakim (PT Mattawang Mediatama Solution, 2024)
This study aims to analyze how factors such as education, age, employment status and gender affect the risk of abnormal working hours (outside the range of 38-42 hours) in Batam City. The data used is secondary data whose data source comes from the Central Bureau of Statistics (BPS) from the National Labor Force Survey (SAKERNAS) in 2022. The number of eligible samples was 3080 family heads. Data processing for analysis in this study used SPSS version 25. The analysis method used is descriptive and inferential analysis. The results revealed that 79.80% of household heads in Batam City work with abnormal working hours. The findings show that education level and age are variables that significantly influence the risk of abnormal working hours. Age variable with the largest odds ratio value is the most influential variable to the risk of abnormal working hours in Batam City. It can be concluded that family heads who have low education level and/or unproductive age can cause the risk of abnormal working hours.